The new pioneers : sustainable business success through social innovation and social entrepreneurship - Ellis, Tania (Cichester, West Sussex ; New York : Wiley, 2010)
"New times create new needs - and new needs require new solutions. The New Pioneers is a practical guide for capitalists and idealists on how to navigate in the new economic world order. It is about the social megatrends that are shaping our lives in new ways and creating a new face of capitalism. And it is about the pioneers that are paving the way for the new business revolution: this century's generation of visionary leaders, social entrepreneurs and social intrapreneurs. 'Hardcore business people are realising that they can increase their profits by incorporating social responsibility into their business, and heartcore idealists are realising that the use of market methods helps them meet their social goals successfully,' argues Tania Ellis. With a wide array of cases from all over the world Tania Ellis explains the key principles of sustainable business success. Read The New Pioneers to gain insight into the new rules that are paving the way for business unusual - for the benefit of humanity and the bottom line."--
"The chief purpose of the book is to show that the concept and principles of social entrepreneurship have potential everywhere, not just among the idealistic few"--
Includes bibliographical references (p. [207]-231) and index.
Keywords: Social entrepreneurship; Social responsibility of business; Twenty first century -- Forecasting